Persepsi Perempuan Bireuen terhadap Rancangan Qanun Poligami di Aceh (Analisis Menurut Teori Self Perception) - Syeh Khaliluddin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This research was conducted in Bireuen Regency, Aceh in 2021 using a qualitative descriptive method based on field research using a self-perception theory approach. This theory serves to analyze how women's perceptions regarding the draft qanun on family law in Aceh regarding polygamy were initiated by the Aceh provincial government through the Islamic Shari'a Service and discussed at the legislative level in August 2019. The number of informants in this study was 100 women who were taken as samples. in 6 sub-districts out of 17 sub-districts in Bireuen Regency. Informants were classified into three social classes consisting of religious, bureaucrats, and business people. The results show that negative perceptions of polygamy regulation are influenced by empirical stimuli and negative stigma in society, where polygamy is attributed as a betrayal and male domination in the household. However, after knowing the substance of the qanun, their perception drastically changed. 60% of informants agree because they perceive that the draft qanun is a regional regulation that can strengthen the existing law on polygamy. Meanwhile, 40% of informants perceive that the draft qanun can motivate a husband to polygamy and the decision of the Sharia Court to give permission for polygamy to the husband if the wife is sick. 5% of informants are antipathy to any issues, even regulations regarding polygamy.